The Development of Interactive Learning Multimedia for Pencak Silat Using Google Sites - Zusyah Porja Daryanto; Suriani Sari; Rino Lusiyono Lucius; Rustam Rustam (JETL (Journal of Education, Teaching and Learning), 2025)
The objective of this study was to develop an Interactive Learning Multimedia on Pencak Silat using the Google Sites platform. The research employed the Research and Development (R&D) methodology with the ADDIE approach. The study involved 39 participants, including academics serving as media and learning experts, an academic validator, a high school teacher as a material expert/practitioner, and 35 Physical Education teachers from the High School Teacher Association of Landak Regency as end users. Data collection tools included observation sheets, interview guidance, questionnaires, and assessment sheets for both experts and users. The data analysis encompassed both qualitative and quantitative methods. The evaluation by the material expert indicated that the product was deemed suitable for use with an excellent qualification. The multimedia expert stated that the product was fitting for use with a good criterion. The learning expert affirmed that the product was suitable for use with an excellent qualification. User assessments also resulted in excellent qualifications. Based on the research findings, the conclusion is drawn that the Google Sites platform of Interactive Learning Multimedia for Pencak Silat is well-suited for educational purposes. The utilization of this interactive multimedia in learning is highly adaptable to the demands of the modern era, enabling individuals to learn at any time and place without being constrained by space, distance, or time.